Resettlement features of population of Ternopil oblast in the context of new administrative and territorial system - Zablotovska, Natalia; Danilova, Olha; Salii, Mykhailo (Human Geography Journal, 2022)
The study is devoted to the study of territorial differences in the resettlement of the population of Ternopil oblast after the introduction of changes in the administrative-territorial structure of the oblast, as one of the oblast regions where the boundaries and centers of the new administrative raions practically coincided with their eponymous inter-district resettlement systems. After all, as a result of the change in the administrative-territorial system, we received a certain redistribution of the population within the basic units of resettlement systems, and they are the beginning of those irreversible changes in resettlement systems that we will observe in the coming years. The article calculates and analyzes indicators-characteristics of population placement at the level of territorial communities of the oblast. The author uses the indicators of area of administrative units and their population, population density, the average distance between settlements, the coefficient of urbanization and the share of the urban population, the population concentration index and the degree of development of connections between the centers of territorial communities, as an indicator of the future prospects of cooperation between newly formed administrative centers. According to all the analyzed characteristics, at the raion level, Ternopil raion takes the leading position, and it was formed on the basis of the inter-district resettlement system of the same name. While Kremenets acts as an outsider. Which is expected, taking into account the peculiarities of the development of the Ternopil subregional resettlement system. But studies at the level of territorial communities, which actually have become the basis of new resettlement systems at the local level, have shown qualitative advantages in the resettlement characteristics of communities that form the supporting framework of resettlement in Ternopil oblast. The obtained results showed that the existing disproportions in the resettlement of the population of the study region, with the implementation of the new administrative-territorial system, have not only remained, but will intensify in the future. As a result of the analysis of all the above-mentioned indicators-characteristics of resettlement, the determining role of centers former inter-raion resettlement systems and separate centers of bush-level resettlement systems can be traced.